Exploring Australian pharmacists' perceptions and attitudes toward codeine up-scheduling from over-the-counter to prescription only - Melanie McKenzie; Jacinta Johnson; Karen Anderson; Richard Summers; Pene Wood (Centro de Investigaciones y Publicaciones Farmaceuticas, 2020)
Objective: Explore the perceptions, attitudes and experiences of pharmacists relating to the up-scheduling of low dose codeine containing analgesics and the impact on pharmacy practice. Methods: A mixed design method was used consisting of an anonymous online questionnaire survey to quantitatively capture broad pre-scheduling change perceptions paired with a series of in-depth post-scheduling semi-structured interviews to provide a qualitative picture of the impact of codeine up-scheduling on pharmacy practice in Australia. Results: A total of 191 pharmacists completed the quantitative survey and 10 participated in the in-depth interview. The majority of respondents supported the decision to up-schedule over-the-counter combination products containing codeine to some degree. Three main themes emerged from the data: pharmacists' perceptions of the codeine up-scheduling decision, preparing for the up-schedule and impact of the up-schedule on pharmacy practice. Pharmacists were concerned about the impact of up-scheduling on the pharmacy business, patient access to pain relief and the diminishment of their professional role. Conclusions: There were diverse perceptions, preparedness and impact on practice regarding the up-scheduling of low dose codeine products. Further research should be conducted to gauge if and how these perceptions have changed over time and to identify whether pain is being managed more effectively post codeine up-scheduling.